Phenotypic Evaluation of Crossbred Progeny from Boer and Peranakan Ettawa (PE) Goats - Kentjonowaty, Inggit; Suyadi, Suyadi; Chabiburrochman, Muhammad Masud (Jurnal Ilmu-Ilmu Peternakan, 2026)
Given the importance of enhancing local livestock productivity, this study evaluated the phenotypic traits of Boer × Peranakan Ettawa (Boer-PE) crossbred offspring. The objective was to identify superior individuals for the development of a specialized meat-type goat lineage in Indonesia. Nineteen Boer-PE offspring, consisting of nine females and ten males, were monitored from birth to four weeks of age. Morphometric data, including body weight, body length, wither height, chest circumference, and ear dimensions, were recorded and analyzed to identify the performance of their parental breeds. The results showed that the crossbred progeny had higher average body weight and improved morphometrical attributes as compared to the native PE goats, which indicated the presence of positive heterosis. Female offspring Boer-PE goats had the average weight gain of 1.8 kg, with chest circumference of 36.86 cm, body height of 36 cm, and body length of 36 cm. Males offspring showed higher performance, with an average weight gain of 2.0 kg, chest circumference of 39.13 cm, body height of 42.25 cm and body length of 39.13 cm. These findings showed that Boer-PE crossbred goats have significant potential in the selection as the starting stock in meat type goat breeding initiatives. It is recommended to carry out further generational analysis in conjunction with molecular genetic research to confirm that the performance is stable, and that the beneficial traits are hereditary.